SIRT2 deficiency prevents age-related bone loss in rats by inhibiting osteoclastogenesis - Jing, Yixuan; Zhou, Yanman; Zhou, Feiye; Wang, Xiaofeng; Tao, Bei; Sun, Lihao; Liu, Jianmin; Zhao, Hongyan (Cellular and Molecular Biology, 2019)
Sirtuin 2 (SIRT2) is a deacetylase that belongs to class III family of histone deacetylases (HDACs). Although it is the most abundantly expressed member of HDAC-III in human bone tissues, it is unclear whether SIRT2 plays a role in bone metabolism. In this study, the role of SIRT2 in bone metabolism, and the underlying mechanism were investigated. In in vivo experiments, micro-CT analysis revealed that there were no differences in bone microstructures between SIRT2-KO and WT rats at 12 weeks of age. However, in 36-week-old rats, increased Tb. BMD, bone volume fraction (BV/TV) and trabecular number (Tb. N) of distal femurs were observed in SIRT2-KO rats, when compared with those of WT rats. Moreover, reduced serum Î²-CTX was identified in the 36-week old rats. In in vitro studies, inhibition of SIRT2 with its specific inhibitor, AGK2, suppressed the differentiation of bone marrow-derived mononuclear cells (BMMs) into osteoclasts via reduction of the expressions of c-Fos and NFATc1. These results suggest that SIRT2 plays a role in age-related bone loss, probably by regulating osteoclastogenesis.